Isoniazid pharmacokinetics/pharmacodynamics as monotherapy and in combination regimen in the hollow fiber system model of Mycobacterium kansasii. (January 2023) - Boorgula, Gunavanthi D.; Singh, Sanjay; Shankar, Prem; Gumbo, Tawanda; Heysell, Scott K.; Srivastava, Shashikant
Abstract: Background: There is limited high quality evidence to guide the optimal doses of drugs for the treatment of Mycobacterium kansasii pulmonary disease ( Mkn -PD). Methods: We performed (1) minimum inhibitory concentration experiment, (2) isoniazid dose-response study using the hollow fiber system model (HFS- Mkn ) to determine PK/PD optimized exposure, and (3) another HFS- Mkn study to determine the efficacy of high dose isoniazid (15 mg/kg/day) with standard dose rifampin (10 mg/kg/day) and ethambutol (15 mg/kg/day). Inhibitory sigmoid maximal effect model and linear regression was used for data analysis. Results: MIC of the 20 clinical isolates ranged between 0.5 mg/L to 32 mg/L. In the HFS- Mkn, isoniazid monotherapy failed to control the bacterial growth beyond day 7. On day 7, when the maximal Mkn kill was observed, the optimal isoniazid exposure for Mkn kill was calculated as 24hr area under the concentration-time curve to the MIC of 12.41. Target attainment probability of 300 mg/day dose fell below 90% above the MIC of 1 mg/L. High dose isoniazid combination sterilized the HFS- Mkn in 30-days with a kill rate of −0.15 ± 0.02 log10  CFU/mL/day. Conclusion: Despite initial kill, isoniazid monotherapy failed due to resistance emergence. Our pre-clinical model derived results suggest that higher than currently recommended 300 mg/day isoniazid dose may achieve better clinical efficacy against Mkn -PD. Highlights: Global scatter of patients is a challenge in performing randomized controlled trials for  M. kansasii. Optimal dose of drugs in combination regimens for treatment of  M. kansasii  maybe different from those for  M. tuberculosis . In the pre-clinical model isoniazid 300mg/day dose failed to kill M. kansasii due to emergence of drug resistance. Higher isoniazid dose is required for better therapy outcome of M. kansasii pulmonary disease.